Impact of continuous glucose monitoring with diabetic education on glycemic variability and HbA1c - Varughese, Mohan; Mathew, Riju; Varghese, Jessy; Chacko, Cheryln Ann; Augustine, Dona V. (International Journal of Advances in Medicine, 2020)
Background: Continuous glucose monitoring (CGM) is an invasive technique which can be used in both outpatient and inpatient settings and can be used for assessing the glycemic variability among individuals with diabetes. It is an effective tool in diabetic management for evaluating the hypoglycemic, hyperglycemic and euglycemic events. Methods: The study was both retrospective and prospective which was conducted at Believers Church Medical College Hospital, Thiruvalla after getting approval from the institutional ethical committee and patient consent was also taken. Patients with uncontrolled diabetes and those with suspicion of hypoglycaemia were taken from the patients attending the diabetic clinic from 26 July 2017. The study duration was from 26 July 2017 to 19 October 2019 (2 years). Results: The study revealed the importance of CGM in the therapeutic management of diabetic patients by monitoring the individual patients and leading to an individualization of therapeutic regimen. It also helped to analyse the effect of each antidiabetic agent in the individual patients and thereby preventing the further occurrence of hypoglycemic and hyperglycemic stages in the individuals and will help to maintain a euglycemic stage in each individual and thus improving the patient’s quality of life. Conclusions: Hence it is concluded from this study that CGM has an important role in the better therapeutic management in diabetic patients as it helps in individualisation of therapy based on each patient in a better glycaemic control leading to a euglycemic state resulting in statistically significant HbA1c reduction.